The Research of an Automatic Phase Displacement Island Protection Method of Photovoltaic Power Generation System - WANG Yu-xin; ZHANG Feng-ge; LI Lin-lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper proposes a lonely island detection method based on automatic type phase displacement. Different form the traditional island detection methods, this method solve the problem of its some kind of detection under the condition of failure , improving active island detection technology of slip type automatic frequency quadratic displacement method. This method only need to change the output current of the initial angle without changing its frequency to detect whether the grid failure, compared with the traditional island detection methods, improve the accuracy of the grid fault detection. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4173